The Impact Of Some Demographic Variables On Educational Crisis Management "A Field Research At The First Cycle Schools Of The Basic Learning In Lattakia" - ناصر, رشا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to identify the level of existence of educational crisis management at the first cycle schools of the basic learning In Lattakia, it aims also to identify the impact of some demographic variables (Job title, gender, number of years of experience, educational and educational qualification, school location, training courses) on Educational Crisis management at the first cycle schools of the basic learning, This research adopts the descriptive approach, and it uses a questionnaire that consists of (27) phrases as a tool to collect data from the sample of the research which consists of (242) administrators in the first cycle schools of the basic learning in Lattakia (2018- 2019). Results have shown that the educational crisis management was present to a high level, with relative weight (78%). As indicated by results the degree of educational crisis management in the first cycle of basic education schools affected by variables (school location, scientific and educational qualification, job title, training courses).